2003
DOI: 10.1182/blood-2003-01-0166
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of plasminogen activation: a role for melanotransferrin (p97) in cell migration

Abstract: We recently reported that human recombinant melanotransferrin (p97) presents a high transport rate across the bloodbrain barrier that might involve the lowdensity lipoprotein receptor-related protein (LRP). We now report new interactions between p97 and another LRP ligand, the urokinase plasminogen activator (uPA) complex. By using biospecific interaction analysis, both pro-uPA and plasminogen are shown to interact with immobilized p97. Moreover, the activation of plasminogen by pro-uPA is increased by soluble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 43 publications
2
37
0
1
Order By: Relevance
“…However, the identities of cell surface binding sites for Plg have not been completely elucidated. The interaction between truncated sMTf and plasminogen, and its involvement in plasminogen activation stimulation by scu-PA was previously reported [27,28]. Thus, we now investigate whether mMTf could be a potential cell surface Plg binding and activation protein and determine its involvement in cell migration and invasion, by using control and MTf-transfected CHO cells as well as SK-Mel-28 melanoma cells.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…However, the identities of cell surface binding sites for Plg have not been completely elucidated. The interaction between truncated sMTf and plasminogen, and its involvement in plasminogen activation stimulation by scu-PA was previously reported [27,28]. Thus, we now investigate whether mMTf could be a potential cell surface Plg binding and activation protein and determine its involvement in cell migration and invasion, by using control and MTf-transfected CHO cells as well as SK-Mel-28 melanoma cells.…”
Section: Discussionmentioning
confidence: 71%
“…Recent studies from our laboratory showed that truncated sMTf interacts with Plg and stimulates its activation by u-PA in vitro [27,28]. Here, the influence of mMTf expression on Plg binding at the cell surface was measured (Fig.…”
Section: Mmtf Expression In Cho Cells Stimulates Cell Surface Plasminmentioning
confidence: 98%
See 1 more Smart Citation
“…The observation that a protein involved in iron metabolism has a particular membrane localization is not novel because previous studies have shown that melanotransferrin, a transferrin homologue that binds iron, is attached to the cell surface via a GPI anchor (Food et al, 1994;Kennard et al, 1995). Interestingly, the function of melanotransferrin does not seem to be restricted to its capacity to act as an iron donor; indeed, membrane-bound melanotransferrin fulfils a regulatory function at the level of condrogenesis, angiogenesis, cell migration and tissue plasminogen activation (Sala et al, 2002;Demeule et al, 2003). Similarly, recent studies on TfR2, mainly based on the analysis of TfR2 mutant mice, indicate that TfR2 may function as a sensor of iron-saturated transferrin in the liver, where it acts upstream of hepcidin in the regulatory pathway of iron homeostasis (Kawabata et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…4 Previous in vitro studies demonstrated that, although MTf could bind Fe, it did not efficiently donate it to the cell. [10][11][12][13] Many roles have been proposed for MTf, including transcytosis of Fe across the blood brain barrier, 14,15 angiogenesis, 16 cell migration, 16,17 plasminogen activation, 17 chondrogenesis, 18 eosinophil differentiation, 19 and Alzheimer's disease. 9,20 However, proof for the functional role of MTf is lacking.…”
Section: Introductionmentioning
confidence: 99%